Human FN1 is regulated by the heat-shock response - Dhanani, Karim Colin Hassan (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2015)
Heat shock protein 90 (Hsp90) and heat shock factors (HSFs) are known to be involved in the epigenetic regulation of several fundamental oncogenic genes. Fibronectin (FN) is an extracellular matrix (ECM) glycoprotein which plays key roles in cell adhesion and migration. Hsp90 binds directly to FN and Hsp90 inhibition has been shown to regulate FN protein levels and matrix formation. Where inhibition of Hsp90 with a C-terminal inhibitor (novobiocin) induced the loss of FN matrix, treatment with an N-terminal inhibitor (geldanamycin) increased FN matrix levels. GA treatment induced a strong dose and time dependent increase in FN1 promoter activity and increased total FN mRNA respectively. By contrast, NOV showed no increase in the promoter activity and no change in the expression of FN mRNA. As GA is known to induce the stress response, we investigated the relationship between the cell stress machinery and the transcriptional regulation of FN. Three putative heat shock elements (HSEs) were identified in the FN1 promoter. The loss of two of the three identified putative HSEs resulted in a loss in the basal transcriptional activity of the FN1 promoter in our reporter model. This was in addition to the loss of the induction of transcriptional activity with GA treatment observed with the full-length promoter. Binding of HSF1 to one of the putative HSEs, which was identified as potentially functional from the truncation analysis, was confirmed using ChIP. The occupancy of this HSE by HSF1 was shown to increase with GA treatment. These data support the hypothesis that FN1 is a functional HSF1 target gene. The 5' promoter regions of seven additional ECM protein encoding genes were analysed and mRNA levels were detected by quantitative RT-PCR upon treatment with GA. Collagen 4 _2 and laminin _3 mRNA were found to increase in the presence of GA, whereas collagen 4 _3 and osteopontin showed no change. Similarly to FN1, these data indicate that a subset of ECM genes may be under the regulation of the HSF1 mediated heat-shock response. This may have implications for our understanding of ECM dynamics in cancer, where the clinical application of Hsp90 inhibitors is intended. Additionally, our data provide a poten- tial underpinning for the role of the HSF1 mediated heat-shock response in several fibrotic and metabolic stress related pathologies.
Keywords: Fibronectins; Heat shock proteins; Cancer -- Control; Extracellular matrix